Stability of prestressed stayed steel columns with a three branch crossarm system. (July 2016) - Li, Pengcheng; Wadee, M. Ahmer; Yu, Jialiang; Christie, Nathan G.; Wu, Minger
Abstract: Analytical and numerical investigations of the stability of prestressed stayed columns with three crossarms branching laterally and symmetrically are presented. It is shown that modal symmetry is broken automatically if the critical mode is antisymmetric, which distinguishes it from the stayed columns studied hitherto. The governing imperfection distribution that should be adopted within finite element analysis to capture the actual load-carrying capacity is also obtained. The findings suggest that when the critical buckling mode is symmetric, the governing imperfection distribution should also be symmetric. Conversely, if the critical buckling mode is antisymmetric, a symmetric imperfection distribution or an asymmetric imperfection distribution may be adopted as the most severe imperfection distribution depending on the system characteristics. This would enable designers to determine an accurate prediction of the actual strength through nonlinear finite element analysis. Highlights: Analytical and numerical study of geometrically perfect and imperfect prestressed stayed columns. Focus on the case with a three-crossarm system at midspan. Orientation of worst case imperfection identified. Interactive buckling identified as being automatically triggered when antisymmetric mode is critical. High sensitivity to geometric imperfections is found and a high level of initial prestress is recommended.